Unifying Einstein and Palatini gravities - Amendola, Luca; Enqvist, Kari; Koivisto, Tomi (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We consider a novel class of f(R) gravity theories where the connection is related to the conformally scaled metric ˆgμν=C(R)gμν with a scaling that depends on the scalar curvature R only. We call them C theories and show that the Einstein and Palatini gravities can be obtained as special limits. In addition, C theories include completely new physically distinct gravity theories even when f(R)=R. With nonlinear f(R), C theories interpolate and extrapolate the Einstein and Palatini cases and may avoid some of their conceptual and observational problems. We further show that C theories have a scalar-tensor formulation, which in some special cases reduces to simple Brans-Dicke-type gravity. If matter fields couple to the connection, the conservation laws in C theories are modified. The stability of perturbations about flat space is determined by a simple condition on the Lagrangian.